Enhanced emissions in Tb3+-doped oxyfluoride scintillating glass ceramics containing BaF2 nanocrystals - Huang, L.; Jia, S.; Li, Y.; Zhao, S.; Deng, D.; Wang, H.; Jia, Guohua; Hua, Y.; Xu, S. (Elsevier, 2015)
Transparent Tb3+-doped glass ceramics containing BaF2 nanocrystals were prepared by melt-quenching method with subsequent heat treatment. The XRD and EDS results showed the precipitated crystalline phase in the glass matrix was BaF2. Under 376 nm light, Tb3+ doped oxyfluoride glass ceramics containing BaF2 nanocrystals showed more intense green emission than the as-made glass, and the emission intensity increased with increasing heat treatment temperature and time. The lifetimes of 541 nm emission of Tb3+ doped oxyfluoride glass ceramics were longer than that of as-made glass, which are in the range from 3.00 ms to 3.55 ms. Under X-ray excitation, the green emission was enhanced in the glass ceramics compared to the as-made glass. The results indicate Tb3+ doped oxyfluoride glass ceramics containing BaF2 nanocrystals could be a material candidate for X-ray glass scintillator for slow event detection.